The multi-level effects of corporate entrepreneurial orientation on business unit radical innovation and financial performance. Issue 1 (February 2021) - Hughes, Mathew; Chang, Yi-Ying; Hodgkinson, Ian; Hughes, Paul; Chang, Che-Yuan
Abstract: Corporate enterprises must support its business units to adapt to changes that are increasingly dramatic and complex. In response, corporate entities must organize to embed a corporate entrepreneurial orientation (EO) that pervades the actions of its business units to create the radical innovations needed to thrive in these circumstances. By developing a global willingness–local ability framework, we test a multi-level model of corporate EO by conceptualizing its effects on business unit radical innovation and business unit financial performance, moderated by business unit R&D resourcing and business unit absorptive capacity. With data from 2820 business units of 1290 Taiwanese corporations from two separate surveys, we find support for our theoretical expectations and contribute much-needed knowledge of the multi-level effects of EO and the conditions to turn EO into actual innovation activity and profit from it.